Estudio del suero de leche en la alimentación de cerdos en etapa de levante (destete) - Guanuchi Castro, Holger Ismael (2022)
The objective of this bibliographic research is to provide information on the use of whey as a supplement in the feeding of pigs in the rearing stage (weaning). Therefore, pig farming is an activity that generates several economic incomes; however, the production costs are high and can represent between 60 to 80% of the total cost, due to the high prices of the products used in the feed. Weaning is a critical practice in the productive life of pigs, since it is carried out after three weeks of age, in which the development of the digestive tract is not complete, because it is structurally and functionally complete at 8 weeks after birth, so the sudden change in food from liquid to solid affects the growth of the intestinal villi, reducing the assimilation of nutrients. Whey is a protein-rich by-product because it contains 20% of total milk protein and can replace up to 50% of the balanced diet (21% protein) of pigs. Which makes it a good food alternative, since whey influences the growth of the intestinal villi, resulting in a better assimilation of nutrients, but according to the research cited, whey shows a greater incidence in weight gain in the raising stage, but not at the end of its productive stage, since it only reduces production costs.